THE ERROR ANALYSIS IN USING TENSES MADE BY STUDENTS IN ENGLISH TEACHING AND LEARNING PROCESS - Herawati Bukit (Program Studi Pendidikan Bahasa Inggris, FKIP - Universitas Iskandar Muda, 2020)
We can find term “Error Analysis” in language. These errors could make misunderstanding of English sentence meaning. Tense is a rule when we want to explain our activities and events in written text. As we are academic students, we must have full understanding about tenses, because if we don’t do it, there is much miscommunication that we got. But students don’t have full understanding about this problem. They assume tense as a big burden. It is a real phenomenon that the researcher found. The goal of this researchwas the students’ progress and every student’s level in understanding tenses. The method of this research used quantitative method. Kinds of errors made by second grade students of Health Information Management in using tenses are omission 50% (omission of simple present tense 50%). The percentage errors of using tenses are simple present 50%, simple past 35% and simple future tense 15%. Students should pay attention seriously in learning tenses because tenses are part of grammar.